Marital quality among women with breast cancer: the role of marital intimacy and quality of life - Moreira, Helena; Crespo, Carla; Pereira, Marco; Canavarro, Maria Cristina (Psicooncología, 2010)
Objective: this study aimed to analyze changes in woman’s perceived marital quality and intimacy (communication and engagement dimensions) throughout the breast cancer trajectory. We also sought to explore differences between patients and controls on these variables, as well as to investigate the predictive role of initial intimacy and quality of life (QoL) on marital quality 6 months after the treatment’s ending. Methods: the sample comprises of 47 breast cancer patients and 90 community controls. Data from the patients’ group were collected at two time points: following breast surgery (T1) and 6 months after treatments had ended (T2). The perceived marital quality before the disease was also retrospectively assessed. The following measures were used: WHOQOLBREF (psychological and social QoL); PAIR (communication and engagement) and a singleitem to assess perceived marital quality. Results: There was an increase in perceived marital quality from the retrospective assessment to T1, and no differences were found throughout the disease. With respect to intimacy, only communication decreased over time. When compared with controls, patients presented higher scores on communication and engagement dimensions (T1). A higher marital quality at T2 was predicted by a higher initial psychological QoL and higher initial levels of communication. Conclusions: the diagnosis of breast cancer does not appear to be associated with a decline in marital quality. Moreover, our findings highlighted the importance of sharing with a partner the cancer-related information, as well as the importance of maintaining a good psychological QoL at the beginning of the disease.